ANOPHELES MICROBIOTA IN MALARIA VECTOR AND THE EFFECT ON PARASITE TRANSMISSION - Dita Paramytha Agustin; Berlian Permata Dewi Erlambang; Cizein Tri Cahyanti; Syubbanul Waton; Rike Oktarianti; Kartika Senjarini (BIOEDUKASI, 2021)
Malaria is a vector-transmitted disease with a high number of cases. Plasmodium parasites are transmitted from the body of the Anopheles mosquito to the host through several mosquito organs, including the salivary glands and the midgut. The salivary glands and the midgut, apart from being a breeding ground for parasites, are known from several studies that various types of microbiota inhabit these two organs. The group of bacteria is the most widely known to be associated with Anopheles mosquitoes. The bacteria found were dominated by Gram-negative bacteria, with Pseudomonas being the most common, followed by Aeromonas, Asaia, Comamonas, Elizabethkingia, Enterobacter, Klebsiella, Pantoea, and Serratia. The group of Gram-positive bacteria was represented by the genera Bacillus, Streptococcus, Lactobacillus, and Staphylococcus. Each species of Anopheles has a different composition of associated bacteria. Anopheles-associated bacteria currently receive much attention because of their role in fighting Plasmodium infection. The ability of malaria vector-associated bacteria to inhibit and fight Plasmodium infection is divided into three mechanisms. Bacteria can triger an immune response through the Immune-deficiency (IMD) pathway, which causes active anti-Plasmodium and the production of antimicrobial peptides, increasing ROS synthesis and microbiota, which trigger hemocyte differentiation to protect against Plasmodium. This function related to inhibiting Plasmodium development needs further research so that later it can become an option for vector-based malaria control without damaging the sustainability of the environment.